Supported catalyst with sub-nanocluster active center, preparation method and application of supported catalyst in selective dehydrogenation of isopropanol

By designing a supported catalyst with subnano cluster active center, the problem of deep oxidation of existing catalysts in alcohol oxidation reactions is solved, efficient selective dehydrogenation within a wide temperature window is achieved, and acetone generation rate is significantly improved.

CN119633810AActive Publication Date: 2025-03-18XI AN JIAOTONG UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411903525.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing supported noble metal-based catalysts are prone to deep oxidation in the oxidation reaction of alcohol-based organic compounds, resulting in a decrease in the selectivity of high-valued products and it is difficult to maintain the stability of the selective oxidation products at high temperatures.

Method used

A supported catalyst with subnano cluster active center was designed and prepared, and a single atomic catalyst with a uniform coordination structure was synthesized by step-by-step step-down vacuum extraction method and two-step pyrolysis method, and aligned in directions on the support surface using the ionization effect of non-thermal plasma, so as to achieve precise regulation of metal atom migration rate and agglomeration size.

Benefits of technology

In a wide temperature window (100-200°C), the catalyst can maintain the yield of acetone in the isopropanol dehydrogenation product above 90%, and the acetone generation rate at 180°C is 18.3 times higher than that of traditional catalysts, avoiding deep oxidation of isopropanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633810A_ABST
    Figure CN119633810A_ABST
Patent Text Reader

Abstract

The invention discloses a supported catalyst with a sub-nanocluster active center, a preparation method and an application of the supported catalyst in selective dehydrogenation of isopropanol, the preparation method comprises the following steps: uniformly mixing a noble metal precursor solution with a carrier, carrying out rotary evaporation treatment by adopting a step-by-step depressurization vacuum extraction method, then carrying out primary roasting, and carrying out secondary roasting to obtain the supported catalyst with the sub-nanocluster active center. Powder is obtained; performing plasma discharge treatment on the powder under mixed gas of hydrogen and argon to obtain a sample; and carrying out secondary roasting on the sample. The selective activation of C-H bonds of isopropanol molecules and the rapid desorption of acetone reaction intermediates are synergistically realized through the strong coupling effect and the synergistic catalysis effect among metal atoms with uniform coordination structures on sub-nanocluster sites, so that the deep oxidation of the isopropanol molecules is avoided. The catalyst shows excellent catalytic efficiency in an isopropanol selective dehydrogenation reaction, and the yield of acetone in an isopropanol dehydrogenation product can be kept at 90% or above under a wide temperature window (100-200 DEG C).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of air pollution control, and particularly relates to a supported catalyst with sub-nano cluster active centers, a preparation method and application of the catalyst in selective dehydrogenation of isopropanol. Background Art

[0002] Alcohols such as isopropanol and ethanol are widely used as solvents. Such volatile organic compounds (VOCs) are characteristic pollutants in the packaging, printing, pharmaceutical and other industries. The selective oxidation of alcohol small molecules into aldehydes or ketones can not only provide a synthesis technology for key intermediates for the pharmaceutical and fine chemical industries, but also reduce CO2 emissions due to its incomplete catalytic oxidation, providing a theoretical basis for the coordinated control of industrial waste gas pollution reduction and carbon reduction. However, due to the high bond energy of the C–H bond and the similar electronegativity of the C and H atoms, it is still a great challenge to achieve efficient activation and selective cleavage of β-C–H bonds under mild conditions. Supported noble metal-based catalysts are widely used in catalytic oxidation reactions due to their excellent catalytic activity, but due to the uneven particle size distribution and coordination structure of their active centers, they are very likely to cause deep oxidation of alcohol organic compounds, resulting in reduced selectivity of high-value products.

[0003] Taking the selective oxidation of alcohols as an example, supported noble metal-based catalysts show high alcohol oxidation activity, but tend to deeply oxidize alcohols to CO2 when the temperature rises. The high conversion rate of alcohol molecules at high temperatures will also greatly reduce the selectivity and yield of selective oxidation products. In actual industrial production, even just because of temperature fluctuations, it is easy to destroy the stable and efficient production of selective oxidation products. Therefore, suppressing deep oxidation at high temperatures and then maintaining ultra-high selectivity of selective oxidation products over a wider temperature range is very necessary to achieve a wide temperature window and remains a major challenge for supported noble metal-based catalysts. β-CH bond cleavage has been identified as the rate-determining step for the selective oxidation of alcohols, and the process of deep oxidation to CO2 requires the cleavage of the CC bond. Therefore, the key countermeasure to this challenge is to design catalysts that selectively promote CH bond activation while suppressing CC bond cleavage. However, the bond energies of CH and CC are very close, and it is quite difficult to achieve selective activation of CH alone. Summary of the invention

[0004] In order to overcome the technical problem that the catalyst in the prior art easily causes deep oxidation of alcohol organic compounds, resulting in reduced selectivity of high-value products, the purpose of the present invention is to provide a supported catalyst with sub-nano cluster active centers and a preparation method and its application in the selective dehydrogenation of isopropanol.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a supported catalyst having sub-nano cluster active centers comprises the following steps:

[0007] After the noble metal precursor solution and the carrier are uniformly mixed, a rotary evaporation treatment is performed using a step-by-step pressure reduction vacuum extraction method to obtain a solid;

[0008] The solid is dried and then calcined once to obtain a powder;

[0009] The powder is subjected to plasma discharge treatment in a mixed gas of hydrogen and argon to obtain a sample;

[0010] The sample was calcined twice to obtain a supported catalyst with sub-nano cluster active centers.

[0011] Furthermore, the noble metal precursor is one of chloroplatinic acid, sodium chloropalladate, iridium chloride, ruthenium chloride, rhodium chloride, chloroauric acid and silver chloride.

[0012] Furthermore, the carrier is one of silicon dioxide, aluminum oxide, PCN, titanium dioxide and ceria.

[0013] Furthermore, the usage ratio of the noble metal precursor to the carrier is 0.0001 mol:0.2-1.0 g.

[0014] Furthermore, the temperature of the rotary evaporation treatment is 60-65°C, the rotation speed is 120-140 rpm, and the vacuum decrease rate is 10 mbar·min -1 .

[0015] Furthermore, the primary calcination temperature is 350-400°C, the time is 2-3h, and the heating rate is 1-2.5°C·min -1 .

[0016] Furthermore, the voltage of the plasma discharge treatment is 10-30 kV, the current is 1-2 A, and the time is 30-300 min.

[0017] Furthermore, the secondary calcination temperature is 500-550°C, the calcination time is 3-4h, and the heating rate is 5°C·min -1 The secondary calcination atmosphere was a mixture of hydrogen and argon at 5°C·min -1 The heating rate is increased to 500-550°C.

[0018] A supported catalyst with sub-nano cluster active centers.

[0019] Application of a supported catalyst with sub-nano cluster active centers in the selective catalytic dehydrogenation of isopropanol.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention takes the design and development of sub-nanometer cluster active centers with highly uniform particle size distribution and easily regulated coordination structure as the starting point. First, a bottom-up synthesis strategy is adopted to synthesize a single-atom catalyst with a uniform coordination structure by step-by-step pressure reduction vacuum extraction method and two-step pyrolysis method. Then, the ionization effect of non-thermal plasma is used to induce the above-mentioned uniformly coordinated single-atom sites to undergo directional migration and agglomeration on the carrier surface under a reducing atmosphere under the action of an external field. The metal atom migration rate and agglomeration size are precisely regulated by regulating the discharge power of the plasma and the external field treatment time. Through the strong coupling effect and synergistic catalysis between the metal atoms with uniform coordination structure on the sub-nanometer cluster sites, the selective activation of the CH bond of the isopropanol molecule and the rapid desorption of the acetone reaction intermediate are synergistically achieved, thereby avoiding the deep oxidation of the isopropanol molecule. The catalyst prepared by this invention shows excellent catalytic efficiency in the selective dehydrogenation reaction of isopropanol. It can maintain the yield of acetone in the isopropanol dehydrogenation product at more than 90% in a wide temperature window (100-200°C). The acetone generation rate of this catalyst at 180°C is 18.3 times higher than that of traditional supported catalysts. The present invention breaks through the technical bottleneck of low efficiency of selective dehydrogenation of alcohol molecules by traditional supported precious metal-based catalysts, and provides a scientific basis for resource utilization of high-concentration alcohol waste gas from industrial sources and coordinated control of pollution reduction and carbon reduction. In addition, this synthesis method has good universal application for a variety of precious metals and carriers. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the Pd1 / SiO2 (before plasma treatment) and Pd nc High-angle annular dark field scanning transmission (HAADF-STEM) images of Pd1 / SiO2 catalysts, where (a) is Pd1 / SiO2 (before plasma treatment) and (b) is Pd nc / SiO2 catalyst.

[0023] Figure 2 Pd1 / Al2O3 (before plasma treatment) and Pd nc High-angle annular dark field scanning transmission (HAADF-STEM) images of Pd1 / Al2O3 catalysts, where (a) is Pd1 / Al2O3 (before plasma treatment) and (b) is Pd nc / Al2O3 catalyst.

[0024] Figure 3 is the Pt1 / CeO2 (before plasma treatment) and Pt nc High-angle annular dark field scanning transmission (HAADF-STEM) images of Pt1 / CeO2 catalysts, where (a) is Pt1 / CeO2 (before plasma treatment) and (b) is Ptnc / CeO2 catalyst.

[0025] Figure 4 is the Pd1 / TiO2 (before plasma treatment) and Pd nc High-angle annular dark field scanning transmission (HAADF-STEM) images of Pd1 / TiO2 catalysts, where (a) is Pd1 / TiO2 (before plasma treatment) and (b) is Pd nc / TiO2 catalyst.

[0026] Figure 5 Pd nc / TiO2 catalyst catalytic ethanol selective dehydrogenation activity diagram, where (a) is the isopropanol conversion rate diagram and (b) is the acetone selectivity diagram.

[0027] Figure 6 Pd nc / TiO2 and Pd np Comparison of acetone production rate over selective dehydrogenation of isopropanol catalyzed by / TiO2 (traditional supported Pd-based catalyst). DETAILED DESCRIPTION

[0028] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0029] The present invention constructs a supported noble metal-based catalyst with uniform active center particle size and coordination structure to regulate processes such as molecule adsorption-intermediate activated dehydrogenation-product rapid desorption, thereby promoting the selective dehydrogenation of isopropanol and avoiding its over-oxidation.

[0030] The preparation method of the supported catalyst with sub-nanometer cluster active center of the present invention is based on the design and development of sub-nanometer cluster active center with highly uniform particle size distribution and easily regulated coordination structure. First, a bottom-up synthesis strategy is adopted to synthesize a single-atom catalyst with uniform coordination structure by step-by-step pressure reduction vacuum extraction method and two-step pyrolysis method, and then the ionization effect of non-thermal plasma is used to induce the above-mentioned uniformly coordinated single-atom sites to migrate and agglomerate on the carrier surface under a reducing atmosphere under the action of an external field, and the metal atom migration rate and agglomeration size are precisely regulated by regulating the discharge power of the plasma and the external field treatment time. Through the strong coupling effect and synergistic catalysis between the metal atoms with uniform coordination structure on the sub-nanometer cluster site, the selective activation of the CH bond of the isopropanol molecule and the rapid desorption of the acetone reaction intermediate are synergistically achieved, thereby avoiding the deep oxidation of the isopropanol molecule. The catalyst prepared by this invention exhibits excellent catalytic efficiency in the selective dehydrogenation reaction of isopropanol. It can maintain the yield of acetone in the isopropanol dehydrogenation product at more than 90% within a wide temperature window (100-200°C). The acetone production rate of this catalyst at 180°C is 18.3 times higher than that of traditional supported catalysts.

[0031] The preparation method of the present invention specifically comprises the following steps:

[0032] (1) 0.0001 mol of a noble metal precursor (which may be one of chloroplatinic acid, sodium chloropalladate, iridium chloride, ruthenium chloride, rhodium chloride, chloroauric acid and silver chloride) is dispersed in 10-20 mL of deionized water under ultrasonic vibration.

[0033] (2) Add 0.2-1.0 g of a carrier (which may be one of silicon dioxide, aluminum oxide, PCN (polymer carbon nitride), titanium dioxide and cerium dioxide) to the mixed solution obtained in step (1), and mix evenly under ultrasonic magnetic stirring, with the ultrasonic power set to 40%, the temperature set to 50-65° C., and the stirring speed set to 800-1200 rpm.

[0034] (3) The mixed solution obtained in step (2) is subjected to rotary evaporation by a step-by-step pressure reduction vacuum extraction method, the water area temperature is set to 60-65°C, the rotation speed is set to 120-140 rpm, and the vacuum degree reduction rate is 10 mbar·min -1 .

[0035] (4) Dry the solid powder obtained in step (3) at 60-80°C for 6-12h.

[0036] (5) calcining the solid sample obtained in step (4) at 350-400°C in air atmosphere for 2-3h at a heating rate of 1-2.5°C·min -1 .

[0037] (6) placing the solid powder obtained in step (5) in a glass tube of a plasma reactor and evacuating the reactor, then introducing a mixed gas of 20% hydrogen and 80% argon by volume into the reactor and maintaining the mixture for more than 60 minutes at a flow rate of 100-200 mL min -1 .

[0038] (7) Turn on the plasma discharge device in step (6), set the voltage to 10-30 kV, the current to 1-2 A, and the treatment time to 30-300 min.

[0039] (8) The solid powder obtained in step (7) was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 40-60° C. After centrifugation, the obtained sample was ultrasonically washed twice with 30-50 mL of ethanol-deionized water mixed solution (the volume of ethanol and deionized water was 3:1).

[0040] (9) Dry the sample obtained in step (8) at 60-80°C for 6-12h.

[0041] (10) The sample obtained in step (9) was calcined at 500-550°C in air atmosphere for 3-4 h at a heating rate of 1-2°C·min -1 .

[0042] The supported catalyst with sub-nano cluster active centers prepared by the present invention realizes the selective activation of the CH bonds of isopropanol molecules and the rapid desorption of acetone reaction intermediates through the strong coupling effect and synergistic catalysis between metal atoms with uniform coordination structures at the sub-nano cluster sites, thereby avoiding the deep oxidation of isopropanol molecules. The catalyst prepared by the invention exhibits excellent catalytic efficiency in the selective dehydrogenation reaction of isopropanol, and can maintain the yield of acetone in the isopropanol dehydrogenation product at more than 90% in a wide temperature window (100-200°C). The acetone generation rate of the catalyst at 180°C is 18.3 times higher than that of the traditional supported catalyst.

[0043] The following are specific embodiments.

[0044] Example 1 Pd with sub-nano cluster active centers nc Preparation of SiO2 catalyst

[0045] 0.0271g of sodium chloropalladate was dispersed in 20mL of deionized water under ultrasonic oscillation, and 1.0g of SiO2 carrier was added to the solution and mixed evenly under ultrasonic magnetic stirring. The ultrasonic power was set to 40%, the temperature was set to 60℃, and the stirring speed was set to 1000rpm. The mixed solution was subjected to rotary evaporation by step-by-step pressure reduction vacuum extraction method. The water temperature was set to 60℃, the speed was set to 130rpm, and the vacuum degree drop rate was 10mbar·min -1 The solid powder was then dried at 60 °C for 12 h and calcined at 350 °C in air for 2 h at a heating rate of 2.5 °C min -1 The calcined sample was placed in a plasma reactor glass tube and the reactor was evacuated. Then, a flow rate of 150 mL min -1 A 20% hydrogen-80% argon mixed gas was introduced and maintained for more than 60 minutes, and then the plasma discharge device was turned on and treated for 60 minutes at a voltage of 20kV and a current of 1A. The obtained solid powder was then dispersed in 30mL of dimethyl sulfoxide and ultrasonically washed at 60°C. After centrifugation, the obtained sample was ultrasonically washed twice with 30mL of ethanol-deionized water mixed solution and dried at 60°C for 12 hours. Finally, the dried sample was calcined at 500°C in an air atmosphere for 3 hours, with a heating rate of 1°C·min -1 , and obtain Pd nc / SiO2 catalyst.

[0046] See also Figure 1 In (a) and (b), Figure 1 From the HAADF-STEM images, we can see that a bottom-up synthesis strategy was adopted to synthesize a Pd1 / SiO2 single-atom catalyst with a uniform coordination structure by step-by-step decompression vacuum extraction and two-step thermal decomposition. Subsequently, a Pd with uniform sub-nano cluster active centers was successfully synthesized by non-thermal plasma treatment. nc / SiO2 catalyst.

[0047] Example 2 Pd with sub-nano cluster active centers nc Preparation of / Al2O3 catalyst

[0048] 0.0271g of sodium chloropalladate was dispersed in 20mL of deionized water under ultrasonic oscillation, and 1.0g of Al2O3 carrier was added to the solution and mixed evenly under ultrasonic magnetic stirring. The ultrasonic power was set to 40%, the temperature was set to 60℃, and the stirring speed was set to 1000rpm. The mixed solution was subjected to rotary evaporation by step-by-step pressure reduction vacuum extraction method. The water temperature was set to 60℃, the speed was set to 120rpm, and the vacuum degree drop rate was 10mbar·min -1The solid powder was then dried at 80 °C for 12 h and calcined at 400 °C in air for 2 h at a heating rate of 2.5 °C min -1 The calcined sample was placed in a plasma reactor glass tube and the reactor was evacuated. Then, a flow rate of 150 mL min -1 A 20% hydrogen-80% argon mixed gas was introduced and maintained for more than 60 minutes, and then the plasma discharge device was turned on and treated for 120 minutes at a voltage of 20kV and a current of 2A. The obtained solid powder was then dispersed in 30mL of dimethyl sulfoxide and ultrasonically washed at 60°C. After centrifugation, the obtained sample was ultrasonically washed twice with 30mL of ethanol-deionized water mixed solution and dried at 80°C for 12 hours. Finally, the dried sample was calcined at 500°C in an air atmosphere for 3 hours, with a heating rate of 1°C·min -1 , and obtain Pd nc / Al2O3 catalyst.

[0049] See also Figure 2 In (a) and (b), Figure 2 From the HAADF-STEM images, we can see that a bottom-up synthesis strategy was adopted to synthesize a Pd1 / Al2O3 single-atom catalyst with a uniform coordination structure by step-by-step decompression vacuum extraction and two-step thermal decomposition. Subsequently, a Pd with uniform sub-nano cluster active centers was successfully synthesized by non-thermal plasma treatment. nc / Al2O3 catalyst.

[0050] Example 3 Pt with sub-nano cluster active centers nc Preparation of CeO2 catalyst

[0051] 0.0410g of chloroplatinic acid was dispersed in 20mL of deionized water under ultrasonic oscillation, and 1.0g of CeO2 carrier was added to the solution and mixed evenly under ultrasonic magnetic stirring. The ultrasonic power was set to 40%, the temperature was set to 65℃, and the stirring speed was set to 1200rpm. The mixed solution was subjected to rotary evaporation by step-by-step pressure reduction vacuum extraction method. The water temperature was set to 65℃, the speed was set to 140rpm, and the vacuum degree drop rate was 10mbar·min -1 The solid powder was then dried at 80 °C for 12 h and calcined at 400 °C in air for 3 h at a heating rate of 2.5 °C min -1 The calcined sample was placed in a plasma reactor glass tube and the reactor was evacuated. Then, a flow rate of 200 mL min -1A 20% hydrogen-80% argon mixed gas was introduced and maintained for more than 60 minutes, and then the plasma discharge device was turned on and treated for 120 minutes at a voltage of 30 kV and a current of 2 A. The obtained solid powder was then dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 60°C. After centrifugation, the obtained sample was ultrasonically washed twice with 50 mL of ethanol-deionized water mixed solution and dried at 80°C for 12 hours. Finally, the dried sample was calcined at 550°C in an air atmosphere for 3 hours, with a heating rate of 1°C·min -1 , and get Pt nc / CeO2 catalyst.

[0052] See also Figure 3 In (a) and (b), Figure 3 From the HAADF-STEM images, we can see that a bottom-up synthesis strategy was adopted to synthesize a Pt1 / CeO2 single-atom catalyst with a uniform coordination structure by step-by-step decompression vacuum extraction and two-step thermal decomposition. Subsequently, a Pt with uniform sub-nano cluster active centers was successfully synthesized by non-thermal plasma treatment. nc / CeO2 catalyst.

[0053] Example 4 Pd with sub-nano cluster active centers nc Preparation of TiO2 catalyst

[0054] 0.0271g of sodium chloropalladate was dispersed in 20mL of deionized water under ultrasonic oscillation, and 1.0g of TiO2 carrier was added to the solution and mixed evenly under ultrasonic magnetic stirring. The ultrasonic power was set to 40%, the temperature was set to 65°C, and the stirring speed was set to 1200rpm. The mixed solution was subjected to rotary evaporation by step-by-step pressure reduction vacuum extraction method. The water temperature was set to 60°C, the speed was set to 120rpm, and the vacuum degree drop rate was 10mbar·min -1 The solid powder was then dried at 70 °C for 12 h and calcined at 350 °C in air for 3 h at a heating rate of 2 °C min -1 The calcined sample was placed in a plasma reactor glass tube and the reactor was evacuated. Then, a flow rate of 200 mL min -1 A 20% hydrogen-80% argon mixed gas was introduced and maintained for more than 60 minutes, and then the plasma discharge device was turned on and treated for 200 minutes at a voltage of 30 kV and a current of 2 A. The obtained solid powder was then dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 60°C. After centrifugation, the obtained sample was ultrasonically washed twice with 40 mL of ethanol-deionized water mixed solution and dried at 80°C for 12 hours. Finally, the dried sample was calcined at 500°C in an air atmosphere for 4 hours, with a heating rate of 1°C·min-1 , and obtain Pd nc / TiO2 catalyst.

[0055] See also Figure 4 In (a) and (b), Figure 4 From the HAADF-STEM images, we can see that a bottom-up synthesis strategy was adopted to synthesize a Pd1 / TiO2 single-atom catalyst with a uniform coordination structure by step-by-step decompression vacuum extraction and two-step thermal decomposition. Subsequently, a Pd with uniform sub-nano cluster active centers was successfully synthesized by non-thermal plasma treatment. nc / TiO2 catalyst.

[0056] See also Figure 5 In (a) and (b), Figure 5 The test results of the selective catalytic dehydrogenation activity of isopropanol show that Pd nc The TiO2 catalyst exhibited excellent isopropanol catalytic conversion efficiency and acetone selectivity at 180°C and a space velocity of 36,000-45,000 h -1 Under the conditions of 10-20% oxygen volume concentration, 10000ppm isopropanol can be completely converted, and the selectivity of the product acetone is greater than 90%. This is mainly due to the strong coupling and synergistic catalytic effect between the uniformly coordinated metal atoms at the sub-nano cluster sites, which synergistically achieves the selective activation of the CH bonds of the isopropanol molecules and the rapid desorption of the acetone reaction intermediates, thereby avoiding the deep oxidation of the isopropanol molecules.

[0057] See also Figure 6 ,Depend on Figure 6 The comparison of acetone generation rate shows that Pd nc The acetone production rate of the Pd / TiO2 catalyst at 200℃ is higher than that of the conventional np / TiO2 catalyst increased by 18.3 times.

[0058] Example 5 Isopropanol dehydrogenation performance test of supported catalyst with sub-nano cluster active centers

[0059] The performance of the catalyst for the selective catalytic dehydrogenation of isopropanol was evaluated in a fixed bed reactor (id = 6 mm). 50 mg of the catalyst (40-60 mesh) was mixed with quartz sand at a mass ratio of 1:5 to avoid local overheating during the reaction and heated at 300 °C at 20 mL min -1The oxygen flow rate was 10.0% for 1 hour to remove surface impurities. The raw gas mixture consisted of 10000ppm isopropanol (1.0vol%) + 20.0vol% O2 + N2 (balance gas), where 10000ppm isopropanol was produced by blowing N2 gas from a 20℃ constant temperature water bath. The saturated vapor pressure of isopropanol can be calculated according to the Antoine equation. By controlling 16.7mL·min -1 The total flow rate reaches 36000mL·g -1 ·h -1 The space velocity (SV) of the catalyst was 1.33 W / m. The reactants and products were detected online by gas chromatography (GC-2010, Shimadzu) using a flame ionization detector (FID) and a Stabilwax@-DB capillary column. For each measurement, all catalytic performance data were detected three times under steady-state reaction conditions after being kept at a given temperature for at least 30 min and the average value was taken. In addition, at least three independent measurements were performed on samples from different batches to verify the accuracy and repeatability of the test.

[0060] Example 6

[0061] 0.0001 mol of iridium chloride was dispersed in 10 mL of deionized water under ultrasonic oscillation, and 0.2 g of SiO2 carrier was added to the solution and mixed evenly under ultrasonic magnetic stirring. The ultrasonic power was set to 40%, the temperature was set to 65°C, and the stirring speed was set to 1100 rpm. The mixed solution was subjected to rotary evaporation by step-by-step pressure reduction vacuum extraction method. The water temperature was set to 65°C, the speed was set to 140 rpm, and the vacuum degree drop rate was 10 mbar·min -1 The solid powder was then dried at 60 °C for 12 h and calcined at 390 °C in air for 2 h at a heating rate of 1 °C min -1 The calcined sample was placed in a plasma reactor glass tube and the reactor was evacuated. Then, a flow rate of 100 mL / min was added to the reactor. -1 A 20% hydrogen-80% argon mixed gas was introduced and maintained for more than 60 minutes, and then the plasma discharge device was turned on and treated for 200 minutes at a voltage of 10kV and a current of 1A. The obtained solid powder was then dispersed in 30mL of dimethyl sulfoxide and ultrasonically washed at 40°C. After centrifugation, the obtained sample was ultrasonically washed twice with 45mL of ethanol-deionized water mixed solution and dried at 70°C for 10 hours. Finally, the dried sample was calcined at 540°C in an air atmosphere for 2 hours, with a heating rate of 1°C·min -1 , obtaining a supported catalyst with sub-nano cluster active centers.

[0062] Example 7

[0063] 0.0001 mol of ruthenium chloride was dispersed in 13 mL of deionized water under ultrasonic oscillation, and 1.0 g of CeO2 carrier was added to the solution and mixed evenly under ultrasonic magnetic stirring. The ultrasonic power was set to 40%, the temperature was set to 50°C, and the stirring speed was set to 900 rpm. The mixed solution was subjected to rotary evaporation by step-by-step pressure reduction vacuum extraction method. The water temperature was set to 65°C, the speed was set to 130 rpm, and the vacuum degree drop rate was 10 mbar·min -1 The solid powder was then dried at 80 °C for 6 h and calcined at 380 °C in air for 2 h at a heating rate of 1.5 °C min -1 The calcined sample was placed in a plasma reactor glass tube and the reactor was evacuated. Then, a flow rate of 170 mL min -1 A 20% hydrogen-80% argon mixed gas was introduced and maintained for more than 60 minutes, and then the plasma discharge device was turned on and treated for 100 minutes at a voltage of 30 kV and a current of 2 A. The obtained solid powder was then dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 50°C. After centrifugation, the obtained sample was ultrasonically washed twice with 35 mL of ethanol-deionized water mixed solution and dried at 80°C for 6 hours. Finally, the dried sample was calcined at 530°C in an air atmosphere for 3 hours, with a heating rate of 2°C·min -1 , obtaining a supported catalyst with sub-nano cluster active centers.

[0064] Example 8

[0065] 0.0001 mol of rhodium chloride was dispersed in 16 mL of deionized water under ultrasonic oscillation, and 0.5 g of PCN carrier was added to the solution and mixed evenly under ultrasonic magnetic stirring. The ultrasonic power was set to 40%, the temperature was set to 55 ° C, and the stirring speed was set to 1200 rpm. The mixed solution was subjected to rotary evaporation by step-by-step pressure reduction vacuum extraction method. The water temperature was set to 62 ° C, the speed was set to 140 rpm, and the vacuum degree drop rate was 10 mbar min -1 The solid powder was then dried at 70 °C for 10 h and calcined at 370 °C in air atmosphere for 3 h at a heating rate of 2.0 °C·min -1 The calcined sample was placed in a plasma reactor glass tube and the reactor was evacuated. Then, a flow rate of 200 mL min -1A 20% hydrogen-80% argon mixed gas was introduced and maintained for more than 60 minutes, and then the plasma discharge device was turned on and treated for 300 minutes at a voltage of 25kV and a current of 1A. The obtained solid powder was then dispersed in 30mL of dimethyl sulfoxide and ultrasonically washed at 45°C. After centrifugation, the obtained sample was ultrasonically washed twice with 40mL of ethanol-deionized water mixed solution and dried at 60°C for 12 hours. Finally, the dried sample was calcined at 550°C in an air atmosphere for 3 hours, with a heating rate of 1°C·min -1 , obtaining a supported catalyst with sub-nano cluster active centers.

[0066] Example 9

[0067] 0.0001 mol of silver chloride was dispersed in 20 mL of deionized water under ultrasonic oscillation, and 0.8 g of TiO2 carrier was added to the solution and mixed evenly under ultrasonic magnetic stirring. The ultrasonic power was set to 40%, the temperature was set to 65°C, and the stirring speed was set to 800 rpm. The mixed solution was subjected to rotary evaporation by step-by-step pressure reduction vacuum extraction method. The water temperature was set to 63°C, the speed was set to 120 rpm, and the vacuum degree drop rate was 10 mbar·min -1 The solid powder was then dried at 65 °C for 12 h and calcined at 360 °C in air for 3 h at a heating rate of 2.5 °C min -1 The calcined sample was placed in a plasma reactor glass tube and the reactor was evacuated. Then, a flow rate of 120 mL min -1 A 20% hydrogen-80% argon mixed gas was introduced and maintained for more than 60 minutes, and then the plasma discharge device was turned on and treated for 30 minutes at a voltage of 15kV and a current of 1A. The obtained solid powder was then dispersed in 30mL of dimethyl sulfoxide and ultrasonically washed at 55°C. After centrifugation, the obtained sample was ultrasonically washed twice with 50mL of ethanol-deionized water mixed solution and dried at 75°C for 10 hours. Finally, the dried sample was calcined at 520°C in an air atmosphere for 4 hours, with a heating rate of 2°C·min -1 , obtaining a supported catalyst with sub-nano cluster active centers.

[0068] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0069] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a supported catalyst having sub-nano cluster active centers, characterized in that: After the noble metal precursor solution and the carrier are uniformly mixed, a rotary evaporation treatment is performed using a step-by-step pressure reduction vacuum extraction method to obtain a solid; The solid is dried and then calcined once to obtain a powder; The powder is subjected to plasma discharge treatment in a mixed gas of hydrogen and argon to obtain a sample; The sample was calcined twice to obtain a supported catalyst with sub-nano cluster active centers.

2. The method for preparing a supported catalyst having sub-nano cluster active centers according to claim 1, characterized in that: The noble metal precursor is one of chloroplatinic acid, sodium chloropalladate, iridium chloride, ruthenium chloride, rhodium chloride, chloroauric acid and silver chloride.

3. The method for preparing a supported catalyst having sub-nano cluster active centers according to claim 1, characterized in that: The carrier is one of silicon dioxide, aluminum oxide, PCN, titanium dioxide and cerium dioxide.

4. The method for preparing a supported catalyst having sub-nano cluster active centers according to claim 1, characterized in that: The usage ratio of the noble metal precursor to the carrier is 0.0001 mol:0.2-1.0 g.

5. The method for preparing a supported catalyst having sub-nano cluster active centers according to claim 1, characterized in that: The temperature of the rotary evaporation treatment is 60-65°C, the speed is 120-140rpm, and the vacuum drop rate is 10mbar·min -1 .

6. The method for preparing a supported catalyst having sub-nano cluster active centers according to claim 1, characterized in that: The primary calcination temperature is 350-400℃, the time is 2-3h, and the heating rate is 1-2.5℃·min -1 .

7. The method for preparing a supported catalyst having sub-nano cluster active centers according to claim 1, characterized in that: The voltage of plasma discharge treatment is 10-30 kV, the current is 1-2 A, and the time is 30-300 min.

8. The method for preparing a supported catalyst having sub-nano cluster active centers according to claim 1, characterized in that: The secondary calcination temperature is 500-550℃, the calcination time is 3-4h, and the heating rate is 5℃·min -1 The secondary calcination atmosphere was a mixture of hydrogen and argon at 5°C·min -1 The heating rate is increased to 500-550°C.

9. A supported catalyst having sub-nano cluster active centers prepared by the method according to any one of claims 1 to 8.

10. Use of a supported catalyst having sub-nano cluster active centers prepared according to the method of any one of claims 1 to 8 in the selective catalytic dehydrogenation of isopropanol.

Citation Information

Patent Citations

  • Preparation method of carbon-supported noble metal catalyst

    CN103691428A

  • Gold cluster catalyst and method for producing same

    CN104379253A

  • Silicon carbide hydrophobic catalyst and preparation method

    CN107930621A

  • Single-atom cluster type noble metal integral silk screen catalyst for reducing NO from CO

    CN116116405A

  • Technical method of dehydrogenating alcohols

    CN1415591A